Optimal distributed control of the Cahn–Hilliard–Brinkman system with regular potential. (May 2019) - You, Bo; Li, Fang
Abstract: The main objective of this paper is to study the optimal distributed control of the three dimensional Cahn–Hilliard–Brinkman system with regular potential. We apply recently proved well-posedness and regularity results in order to establish the existence of optimal controls as well as the first-order necessary optimality conditions for an associated optimal control problem in which a distributed control is applied to the fluid flow.